Professional, Spectator, and Olympic Sports in the Context of the Terms Spiritualism and Spirituality, and in the Context of Normative Ethics - Kosiewicz Jerzy (Sciendo, 2015)
The author has used - in his paper - two different expressions related to spirituality in its entirety: that is, spirituality (the spiritual sphere in superficial sense and meaning) and spiritualism (the spiritual sphere in deep sense and meaning). The author presented selected different definitions and manifestations of spirituality and spiritualism.